Phase regulation enabling dense polymer-based composite electrolytes for solid-state lithium metal batteries - Qian Wu; Mandi Fang; Shizhe Jiao; Siyuan Li; Shichao Zhang; Zeyu Shen; Shulan Mao; Jiale Mao; Jiahui Zhang; Yuanzhong Tan; Kang Shen; Jiaxing Lv; et al. (Nature Communications, 2023)
Abstract Solid polymer electrolytes with large-scale processability and interfacial compatibility are promising candidates for solid-state lithium metal batteries. Among various systems, poly(vinylidene fluoride)-based polymer electrolytes with residual solvent are appealing for room-temperature battery operations. However, their porous structure and limited ionic conductivity hinder practical application. Herein, we propose a phase regulation strategy to disrupt the symmetry of poly(vinylidene fluoride) chains and obtain the dense composite electrolyte through the incorporation of MoSe2 sheets. The electrolyte with high dielectric constant can optimize the solvation structures to achieve high ionic conductivity and low activation energy. The in-situ reactions between MoSe2 and Li metal generate Li2Se fast conductor in solid electrolyte interphase, which improves the Coulombic efficiency and interfacial kinetics. The solid-state Li||Li cells achieve robust cycling at 1 mA cm−2, and the Li||LiNi0.8Co0.1Mn0.1O2 full cells show practical performance at high rate (3C), high loading (2.6 mAh cm−2) and in pouch cell.